Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s00535-004-1447-1
|View full text |Cite
|
Sign up to set email alerts
|

Earlier recurrence of esophageal varices, following therapy, in patients with primary biliary cirrhosis (PBC) compared with non-PBC patients

Abstract: We should be extra careful in the follow-up of patients with PBC after therapy for esophageal varices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, nonselective beta-blockers are ineffective in preventing the development of varices in unselected patients with cirrhosis [ 174 ]. There is a report showing earlier recurrence of esophageal varices, following endoscopic therapy, in patients with PBC compared with non-PBC patients [ 175 ].…”
Section: Complications Of Pbc and Their Management (Table 2mentioning
confidence: 99%
“…However, nonselective beta-blockers are ineffective in preventing the development of varices in unselected patients with cirrhosis [ 174 ]. There is a report showing earlier recurrence of esophageal varices, following endoscopic therapy, in patients with PBC compared with non-PBC patients [ 175 ].…”
Section: Complications Of Pbc and Their Management (Table 2mentioning
confidence: 99%
“…Hemorrhage can be a complication of biliary cirrhosis. For example, PBC patients had an earlier recurrence of esophageal varices compared to non-PBC patients and variceal bleeding complicates PBC, when it is histologically advanced [26, 27]. In our study with laser-induced thrombosis, 54 rats were randomly assigned to 4 groups, two of them underwent common bile duct ligation and in the other two bile duct was identified but not ligated.…”
Section: Resultsmentioning
confidence: 99%
“…Since prognosis becomes poor once variceal bleeding occurs 44 and treating esophageal varices is difficult, 50 several groups have attempted to define non‐invasive predictors of esophageal varices in PBC patients 51,52 . Blessler et al.…”
Section: Development Of Esophageal Varicesmentioning
confidence: 99%
“…Since prognosis becomes poor once variceal bleeding occurs 44 and treating esophageal varices is difficult, 50 several groups have attempted to define non-invasive predictors of esophageal varices in PBC patients. 51,52 Blessler et al 51 examined 86 PBC patients and reported that platelet count <200,000/mm 3 , albumin level <4.0 g/dL, and a bilirubin level >20 mmol/L (1.16 mg/ dL) were independent predictors of the development of esophageal varices.…”
Section: Development Of Esophageal Varicesmentioning
confidence: 99%